HUTCHINSON-GILFORD SYNDROME (PROGERIA): A REVIEW - SACHIN KUMAR; AMIT KUMAR; MOHIT SINGLA; ABHISHEK SINGH (International Journal of Pharma and Bio Sciences, 2010)
Progeria, also known as the Hutchinson-Gilford syndrome, is an extremely rare condition that was initially reported by Jonathan Hutchinson in 1886 and further described by Hastings Gilford in 1904. Hutchinson Gilford progeria syndrome is a disorder characterized by premature aging of postnatal onset. The main clinical and radiological features include alopecia, thin skin hypoplasia of nails, loss of subcutaneous fat, and osteolysis. Intelligence is not impaired. Early death is caused by atherosclerosis. Transmission is most likely from a sporadic autosomal dominant mutation. Clinical manifestations are evident by the first or second year of life and include the physical characteristics usually associated with the elderly. Mentally, patients are alert and attentive with normal intelligence and emotions. Histopathologic changes occur primarily in the skin, bone, and cardiovascular tissues, while other organs appear to be unaffected. Laboratory findings are unremarkable, with the exception of an increased urinary excretion of hyaluronic acid. Death results from cardiovascular abnormalities in the majority of cases and usually occurs between the ages of 10 and 15 years.